2011
DOI: 10.3758/s13421-011-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Memory for target height is scaled to observer height

Abstract: According to the embodied approach to visual perception, individuals scale the environment to their bodies. This approach highlights the central role of the body for immediate, situated action. The present experiments addressed whether body scaling-specifically, eyeheight scaling-occurs in memory when action is not immediate. Participants viewed standard targets that were either the same height as, taller than, or shorter than themselves. Participants then viewed a comparison target and judged whether the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In studies investigating tool-use in contrast, the scale of “reaching ability” is typically assumed (e.g., Witt, 2011a). Related scales are “action potential” (e.g., Witt et al, 2008) or “joint size” (Linkenauger, Witt, & Proffitt, 2011), and “eye-height” (Twedt, Crawford, & Proffitt, 2012). What is common to all these concepts, however, is that certain aspects of the perceiver’s body affect perception to the extent that this body is engaged in real, anticipated, or simulated interaction with the environment (cf.…”
mentioning
confidence: 99%
“…In studies investigating tool-use in contrast, the scale of “reaching ability” is typically assumed (e.g., Witt, 2011a). Related scales are “action potential” (e.g., Witt et al, 2008) or “joint size” (Linkenauger, Witt, & Proffitt, 2011), and “eye-height” (Twedt, Crawford, & Proffitt, 2012). What is common to all these concepts, however, is that certain aspects of the perceiver’s body affect perception to the extent that this body is engaged in real, anticipated, or simulated interaction with the environment (cf.…”
mentioning
confidence: 99%
“…If the witness estimates the culprit to be in his/her age group, accuracy in statements is more probable and the attributes can be given more attention. Second, for height estimates, people tend to use eye height scaling (Twedt et al, 2012), meaning that persons showed better accuracy in height estimates when the height of the culprit was not much different from the eye-height of the participant (Twedt et al, 2015). This means that if the eye-height of the witness during the crime was about the same height as the culprit during the crime, a smaller margin of error can be chosen when height estimates are analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This means that if the eye-height of the witness during the crime was about the same height as the culprit during the crime, a smaller margin of error can be chosen when height estimates are analyzed. Also, height estimations seem more accurate if they are done in the same body position as at the time of encoding the height (Twedt et al, 2012). The results of Twedt and colleagues also show that ideally a matching approach (presentation of the pictures are limited to those that match the description) is only used if really necessary; it seems overall better to use a sequencing approach (pictures are sorted that pictures which better match the description are presented earlier) for as many attributes as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that manipulations of visual eye-height relative to postural eye-height affect perceived egocentric distance (Leyrer et al, 2011; Leyrer et al, 2015a, 2015b; Messing & Durgin, 2005; Ooi et al, 2001; Sinai et al, 1998) and size (Bertamini et al, 1998; Dixon et al, 2000; Twedt et al, 2012; Warren & Whang, 1987; Wraga, 1999a, 1999b; Wraga & Proffitt, 2000) of objects in action space (2 m up to 30 m distance from the observer; Cutting & Vishton, 1995). Compared with a condition where visual eye-height matches postural eye-height, perceived object distance increased when visual eye-height was lower than postural eye-height, whereas perceived distance decreased when visual eye-height was higher than postural eye-height.…”
mentioning
confidence: 99%